Can Dreams Come True? Eliminating Extreme Poverty in Africa by 2030 - Mthuli Ncube; Zuzana Brixiova; Zorobabel Bicaba (Institute for the Study of Labor (IZA), 2014)
With the year 2015 – the MDG finishing line – approaching, post-2015 goals as they impact Africa need to be firmed. The goal of ending extreme poverty remains paramount. Globally, the World Bank set goals to end extreme poverty by 2030 and to promote shared prosperity in every society. We examine feasibility of these objectives for Sub-Saharan Africa, the world's poorest but rapidly rising region. We find that under plausible assumptions on consumption growth and redistribution, eliminating poverty by 2030 is out of the region's reach. Even under our 'best case' scenario of accelerated growth and redistribution from the richest 10 percent to the poorest 40 percent of the population, the poverty rate would still be around 10 percent in 2030. A more realistic goal for the region would be reducing poverty by a range from half to two thirds. At this rate, especially if in part achieved by lowering inequality, the Africa region would meaningfully contribute to the global agenda. Policies need to focus on mutually reinforcing objectives of making growth stronger, resilient to shocks, and inclusive.
Keywords: I32; E21; J11; C63; 330; poverty reduction; inequality; inclusive growth; Africa; numerical simulations